2016 38th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2016
DOI: 10.1109/embc.2016.7591146
|View full text |Cite
|
Sign up to set email alerts
|

Design of a bio-inspired pneumatic artificial muscle with self-contained sensing

Abstract: Pneumatic artificial muscles (PAMs) are one of the most famous linear actuators in bio-inspired robotics. They can generate relatively high linear force considering their form factors and weights. Furthermore, PAMs are inexpensive compared with traditional electromagnetic actuators (e.g. DC motors) and also inherently light and compliant. In robotics applications, however, they typically require external sensing mechanisms due to their nonlinear behaviors, which may make the entire mechanical system bulky and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…This actuator is flexible, lightweight and has high force-weight ratio [8]. In addition, the flexibility of both the fibers and the bladder makes it fully compliant [9].…”
Section: Introductionmentioning
confidence: 99%
“…This actuator is flexible, lightweight and has high force-weight ratio [8]. In addition, the flexibility of both the fibers and the bladder makes it fully compliant [9].…”
Section: Introductionmentioning
confidence: 99%
“…In this case, a simple linear function is found that associates the changes in muscle length with those ones of the measured inductance. A similar solution was described in [34], where the external gauze was modified to include an inductive coil surrounding the muscle fibers: the length of the muscle is achieved by measuring the corresponding coil inductance change.…”
Section: Introductionmentioning
confidence: 99%
“…Some prototypes were designed with a sensor placed outside the McKibben muscle. For example, a coil wrapped around the muscle fibers establishes a link between the coil inductance and the muscle contraction [12]. Kuriyama et al and Yamamoto et al placed respectively a flexible ring [13] or film [14] made out of an electro-conductive rubber around a muscle.…”
Section: Introductionmentioning
confidence: 99%